Parents' Management of Privacy Turbulence Surrounding Private, Adoption-Related Information in Transracial, Internationally Adoptive Families. Issue 1 (2nd January 2022) - Loftus, Mary Claire Morr; Suter, Elizabeth A.; Hanna, Michele D.; Strasser, Daniel S.
ABSTRACT: Parents ( N = 166) in transracial, international adoptive (TIA) families with children from China or Vietnam were surveyed to investigate their experiences with privacy turbulence surrounding the family's private, adoption-related information. About half described at least one instance of privacy turbulence, with a total of 98 instances. The instances included examples of all six types of privacy turbulence described in Communication Privacy Management theory, but two of those types, namely boundary rule mistakes and boundary definition predicaments, accounted for 90% of the instances of turbulence. Evidence of explicit rules and catalyst criteria for rule formation in the turbulence descriptions suggest ways that TIA parents might be able to avoid or manage privacy turbulence.